Penerapan Business Intelligence Pada Tiktok dalam Menarik Konsumen Berbelanja di Tiktok Shop - Amelia Aditya Putri; M. Hanif Rafi Farrasi; Prita Prameswari Fauzianti; Rais Hakim Wibowo (Trending: Jurnal Manajemen dan Ekonomi, 2024)
In the era of globalization, technology continues to develop, making it very easy to influence people with the latest trends or innovations, especially young people. With the emergence of TikTok is an example. Today’s technology has undergone many developments and it is an effort to make life easier. One of them is in terms of shopping. The release of online features in shopping makes people spend more time at home than going to the store directly. This research was created with the aim of analyzing TikTok application users in using the TikTok Shop feature. The audience of the live broadcast is one of the TikTok accounts with a saturated sample, namely the research population. Data collected through observations of netizen interactions with shop sellers on Tiktok live broadcasts. This journal was created using a qualitative method based on previous research journals by comparing several journals based on various theories focused on TikTok users who shop at TikTok Shop.